Synagogues without rabbis or Christians? Ancient institutions beyond normative discourses. Issue 2 (4th May 2017) - Runesson, Anders
Abstract: This article focuses on a problem that tends to afflict, especially but not exclusively, historical narratives involving written sources celebrated as normative texts in contemporary religious communities. The religious authority ascribed to such texts is often entangled in claims about historical phenomena, resulting in ideological support of specific narratives nourished within religious communities as not only religiously significant but also historically true. Such assumptions in turn sustain aspects of religious identities and thus fulfil the social function of maintaining the status quo within and between communities. Because of their contemporary usefulness, these types of normative narratives are liable to bleed into scholarly reconstructions too, complicating the academic search for historical scenarios untouched by the needs of societies unknown to the ancients. This study aims to illustrate the problems involved through an exercise in which sources that speak to a specific historical question – the nature of ancient synagogues – but which later attained normative status within religious communities, are removed from the historical archive. The reconstruction offered, based on sources with no direct relationship to the continuing histories of Judaism and Christianity, yields a very different picture than the one commonly embraced today. The exercise also indicates the value of re-reading the sources previously removed from a new perspective, which may enrich the religious communities in question as they seek to understand their own history and identity, as well as one another.